On the Application of Zhenwu Decoction in Renal Edema - Liu, Xiaoxiao; Lei, Ting (Journal of Contemporary Medical Practice, 2024)
This paper aims to explore the application prospect of Zhenwu decoction in renal edema. Methods: Through the review of ancient and modern literature and modern research, the causes and clinical manifestations of renal edema, the composition and effect of adding and decreasing, and the modern research of Zhenwu soup in the treatment of renal edema are discussed. Results: It was found that Zhenwu soup had a better effect on the treatment of renal edema than western medicine, and had little adverse reactions, which could effectively improve the clinical symptoms of patients and the quality of life after recovery. Conclusion: Zhenwu decoction is a very effective method to treat renal edema, with wide application prospect and clinical value.